Liquid Crystal Targets and Plasma Mirrors For Laser Based Ion Acceleration. (27th April 2017) - Schumacher, D.W.; Poole, P.L.; Willis, C.; Cochran, G.E.; Daskalova, R.; Purcell, J.; Heery, R.
Abstract: Practical application of laser based ion acceleration will require advances across a wide range of technologies extending from the laser system itself to the delivery of the ion beam. We have recently shown that the liquid crystal 8CB provides an effective and relatively inexpensive new approach to target and plasma mirror fabrication and insertion for ion acceleration. 8CB is primarily hydrogen and carbon and forms in layers approximately 3 nm thick in its smectic phase. Taking advantage of these properties, we have developed a device we call the Linear Slide Target Inserter (LSTI) that can form films in situ from under 10 nm in thickness to over 50 μ m. We describe this new technology and its operation as a target inserter and as a high-power plasma mirror. For proton acceleration, the LSTI readily achieves energies of 25 MeV using pulses of only a few joules by tuning the target thickness for the specific laser pulse characteristics and pre-pulse contrast. For plasma mirrors, we have demonstrated a weak field reflectivity below 0.2% and a high field reflectivity above 75%, yielding a potential pulse contrast improvement over two orders of magnitude. The LSTI can form films at a rate of several per minute for the thinnest films and we have developed a prototype based on a rotary geometry that has demonstrated a film formation rate up to 3 Hz for ultrathin films (approximatly 10 nm). We also propose the use of high repetition rate liquid crystal based plasma mirrors for debris mitigation. Taken together, these ideas and results suggest that liquid crystal technology could play a key role in the development of robust, high repetition rate, laser based ion sources.